An equity-based framework for defining national responsibilities in global climate change mitigation. (23rd February 2017) - Liu, Lei; Wu, Tong; Huang, Ying
Abstract : As a global public good, climate change cannot be addressed without global cooperation and action, which in turn depends on an equitable distribution of responsibility. There are numerous problems with the United Nations Framework Convention on Climate Change (UNFCCC) for designating national responsibilities for CO2 emissions (NRCE) – including the dispute over the equity of production-based mechanisms and vague definitions of historical emissions. Therefore, it is necessary to re-think the principles that should govern the allocation of NRCE. The essence of the dispute over production- or consumption-based emissions accounting is the distribution of the CO2 trade balance (CTB) between two partners. "Common but Differentiated Responsibilities" (CBDR) provides a foundation for discussing equity in global climate policy. Based on CBDR, this article proposes a rubric of equity principles for defining NRCE: first, there are "horizontal allocation rules", according to which the CTB between trading partners is distributed according to their respective levels of development (as measured by the Human Development Index), emissions per capita and gains from the trade; second, there are "vertical extending rules", according to which the historical emissions of a country are accounted for with reference to the horizontal allocation rules and added to the present-day NRCE of the country. We argue that considering global climate policy coordination in this light will contribute to formulating a more robust definition of NRCE.